HUBUNGAN JUMLAH LEUKOSIT DENGAN LAMA KETUBAN PECAH DINI PADA IBU HAMIL DI RUMAH SAKIT ISLAM SITI RAHMAH PADANG TAHUN 2021-2023 - Prima Della Fegita; Rahmi Syukra Fadilla (Yayasan Nusantara Hasana Berdikari, 2025)
Premature Rupture of Membranes (PROM) can occur spontaneously at a gestational age >37 weeks, referred to as term PROM, and at ≤37 weeks, referred to as preterm PROM. This condition is a serious obstetric problem that can lead to maternal and neonatal infections and complications such as prematurity, morbidity, and mortality. PROM may arise due to infection, marked by leukocytosis. Leukocytosis can be evaluated through blood tests, which are used to monitor the potential for infections during pregnancy. This study aims to investigate the relationship between leukocyte count and the duration of PROM in pregnant women at Siti Rahmah Islamic Hospital, Padang, during 2021–2023. This research employed an analytical observational method with a cross-sectional design, involving simultaneous data collection of variables. The sample size for this study was 99 participants. Statistical analysis using the Kolmogorov-Smirnov test yielded a p-value of 1.000 > 0.05. This indicates that there is no relationship between leukocyte count and the duration of PROM in pregnant women at Siti Rahmah Islamic Hospital, Padang, from 2021 to 2023. There is no significant relationship between leukocyte count and the duration of PROM in pregnant women at Siti Rahmah Islamic Hospital, Padang, during 2021–2023.